Desorption of Per-and Polyfluoroalkyl Substances from Powdered and Colloidal Activated Carbon - Uramowski, Andrew (University of Waterloo, 2024)
Per- and polyfluoroalkyl substances (PFAS) are a group of synthetic chemicals with unique heat-resistant properties, leading to their usage in aqueous film-forming foams (AFFF) for fighting fuel-based fires at airports and military bases. The application of AFFF at these facilities has led to the contamination of groundwater with PFAS, which can threaten the safety of nearby drinking water, agricultural, and industrial supply wells, as well as downgradient surface water bodies. Drinking water supplies contaminated with PFAS can result in human exposure, which has been linked to developmental, immunological, endocrine, and cardiovascular disorders, and cancer. Since PFAS are resistant to biodegradation and traditional destruction technologies, current remediation efforts are focused on immobilizing PFAS using adsorptive processes that sequester PFAS from the aqueous phase, concentrating them on an adsorbent media. The injection of activated carbon (AC) particulate amendments into the subsurface has been suggested as a promising technique for the in situ immobilization of plumes of PFAS and to protect downgradient receptors. To predict the long-term performance of these AC barriers, a thorough understanding of adsorption and desorption processes is required. The objective of this research was to investigate the desorption behaviour of three PFAS (perfluorooctane sulfonic acid (PFOS), perfluorooctanoic acid (PFOA), and perfluorobutane sulfonic acid (PFBS)) from a powdered AC (PAC) and a colloidal AC (CAC). The research focused specifically on assessing whether desorption of PFOS, PFOA, and PFBS on these two AC materials was hysteretic. PFAS adsorption and desorption kinetic experiments using PAC or CAC were completed to determine the contact time required to reach near-equilibrium conditions. Adsorption experiments with PAC utilized the bottle-point method, and desorption experiments used a sequential desorption methodology where the aqueous phase of desorption reactors was replaced with an adsorbate-free solution. Adsorption of PFAS by CAC was also investigated using the bottle-point method; however, desorption experiments were conducted using two different methods: (1) a sub-sampling methodology where aliquots of slurry from a well-mixed adsorption isotherm bottle were diluted to initiate desorption, and (2) a whole-bottle dilution method where the entire contents of adsorption reactors were diluted to larger volumes to initiate desorption. The results indicated that for experiments utilizing PAC, adsorption and desorption equilibrium was established for all compounds within 72 h. Desorption of PFOS, PFOA and PFBS from PAC did not demonstrate hysteresis since all desorption data were contained within the 95% adsorption prediction band. For experiments using CAC, adsorption equilibrium was established by 120 h for all compounds, while desorption equilibrium was established by 120 h for PFOS, and 72 h for PFOA and PFBS. Desorption data using the sub-sampling method for PFOS, PFOA or PFBS and CAC were below and outside of the 95% adsorption prediction band. It was concluded that unrepresentative sub-sampling of CAC slurry occurred in the desorption step using this method. When the whole-bottle dilution method was adopted for PFOS, desorption data were within the 95% adsorption prediction band, indicating no evidence of hysteresis under the experimental conditions used. Since mass removal at each desorption step was extremely small compared to the sorbed fraction, desorption data did not reach aqueous equilibrium concentrations near the method detection limit. The absence of hysteretic behaviour in this research demonstrates that sorption processes are reversible over the concentration ranges explored. This reversibility implies that PFAS sorbed within AC barriers can be released when the groundwater concentration is decreased, either due to temporal heterogeneity in concentration profiles, or the depletion of the source zone.
Keywords: PFAS; per- and polyfluoroalkyl substances; desorption; hysteresis; adsorption; powdered activated carbon; colloidal activated carbon